Pad cultures: An ethnography of continence care and its consequences for people living with dementia during a hospital admission. (October 2022) - Northcott, Andy; Boddington, Paula; Featherstone, Katie
Background: There is little research examining how continence care is organised and delivered to people living with dementia across an acute hospital admission, despite the prevalence of this patient population and their vulnerability within these settings. Objective: To explore how continence care is delivered to people living with dementia during an acute hospital admission. Design: Ethnographic. Setting(s): Acute medical units and wards within three hospitals across England and Wales. Participants: People living with dementia and ward staff (registered nurses and care assistants) on participating wards. Methods: Ethnographic fieldwork collected over a period of 12 months (180 days of non-participant observation) focussing on the organisation and delivery of continence care to people living with dementia. Observations were supported with in situ ethnographic interviews ( n = 562) with patients, visitors and staff within the six observed wards. Data collection and analysis drew on the theoretical sampling and constant comparison techniques of grounded theory. Results: The findings comprised of five overall themes: (1) visibility of continence; (2) rationales of continence care; (3) containment and contagion; (4) consequences of continence care and (5) supporting continence. Conclusions: We introduce the term 'pad cultures' to refer to the established routine use of continence pads in the care of a wider group of people living with dementia (regardless of continence status and independence), with the rationale to provide safeguards, ensure containment and prevent 'accidents' or incontinent episodes. There was an expectation within acute wards that people living with dementia not only wear continence pads but that they also use them.